2007
DOI: 10.1186/1477-3163-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundA majority of primary ovarian neoplasms arise from cell surface epithelium of the ovaries. Although old age and a positive family history are associated risk factors, the etiology of the epithelial ovarian tumors is not completely understood. Additionally, knowledge of factors involved in the histogenesis of the various subtypes of this tumor as well as those factors that promote progression to advanced stages of ovarian malignancy are largely unknown. Current evidence suggests that mitochondrial alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…This arises because of the difficulties in accessing ovarian tissues and other anatomical histology appearances. Given that early stage ovarian cancer has a greater five year survival status than advanced presentation, the difficulty lies in the detection of early malignant or premalignant changes in the ovaries [1, 3]. ROS are short lived oxygen-containing derivatives developed as by-products of normal cellular respiration that help to maintain cellular homeostasis along with the body’s innate antioxidant system [1,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This arises because of the difficulties in accessing ovarian tissues and other anatomical histology appearances. Given that early stage ovarian cancer has a greater five year survival status than advanced presentation, the difficulty lies in the detection of early malignant or premalignant changes in the ovaries [1, 3]. ROS are short lived oxygen-containing derivatives developed as by-products of normal cellular respiration that help to maintain cellular homeostasis along with the body’s innate antioxidant system [1,16].…”
Section: Discussionmentioning
confidence: 99%
“…Further, oxidative stress has been associated with the promotion of many human diseases including various cancers [1, 2, 16, 17, 18]. Specifically, ovarian tumors have known to secrete excessive amounts of ROS leading to increase tumor size [3, 11]. Moreover, the microenvironment generated as a result of oxidative injury may help the compounds evade normal checkpoints to trigger human disease [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to missing screening methods and its aggressive behaviour, a vast number is diagnosed at an advanced stage [2]. Steroid hormones have an influence on ovarian cancer cells [3] and it has been shown that 40–60% of ovarian cancers express estrogen receptor (ER) Îą [4, 5].…”
Section: Introductionmentioning
confidence: 99%